2006
DOI: 10.1097/01.lbr.0000212551.40459.8d
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Expulsion of a Hydatid Cyst During Flexible Bronchoscopy

Abstract: An elderly female presenting with a soft tissue density mass on computerized tomography scan in left lower lobe was taken up for flexible bronchoscopy. During the procedure, she coughed out a 9 by 8 cm saclike structure that was confirmed to be a hydatid cyst. It is a rare event and in the present case obviated the need for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…Although it is reported that usually the membrane is visible in case of ruptured cyst, in the present case membrane was observed in an unruptured cyst 6 . In pulmonary hydatid disease, Chest X-ray shows a clearly defined cyst displaying homogenous opacity in case of an uncomplicated cyst or air meniscus sign, double arch sign or water lily sign in case of a complicated cyst 2,7 …”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Although it is reported that usually the membrane is visible in case of ruptured cyst, in the present case membrane was observed in an unruptured cyst 6 . In pulmonary hydatid disease, Chest X-ray shows a clearly defined cyst displaying homogenous opacity in case of an uncomplicated cyst or air meniscus sign, double arch sign or water lily sign in case of a complicated cyst 2,7 …”
Section: Discussioncontrasting
confidence: 49%
“…Bronchoscopy can contribute to the diagnosis by the visibility of the hydatid membranes or finding hydatid elements in the bronchial washing in case of a ruptured cyst. Bronchoscopic instillation of larvicidal agents 12 or even removal of hydatid cysts bronchoscopically, obviating the need for surgery, has also been reported 7 . In this case we were able to demonstrate the 3 layers of the hydatid cyst on EBUS (Fig.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…1 Iran is one of these endemic areas. 3 We report 1 such case in which a hydatid cyst was diagnosed and also completely removed using a flexible bronchoscope. Pulmonary hydatid cyst commonly involves the right lobe.…”
mentioning
confidence: 98%